Design and Development of a Multi-sensor Monitoring Device for Arm Rehabilitation - Ambar, R.; Ahmad, M. S.; Abdul Jamil, M. M. (International Journal of Integrated Engineering, 2011)
A continuous monitoring process for arm rehabilitation activities are important to provide information of rehabilitation results to be analyzed by therapist. The purpose of monitoring is to help them to improve rehabilitation process. Moreover, a portable and simple home-based rehabilitation device can help patients to improve daily rehabilitation activity. Some previous studies regarding home-based rehabilitation process have shown improvement in promoting human movement recovery. But existing rehabilitation devices are expensive and need to be supervised by physical therapist. Some devices are not so efficient to be used at home due to large size and complex system. In this current work, flex sensor, force sensitive resistors and accelerometer were assessed in order to be implemented as a sensory unit for a portable arm rehabilitation device. Analog signal from the sensors will be conveyed to an Arduino microcontroller for data processing and logging. The results of rehabilitation activity can be used for further monitoring and analysis. Experiments were carried out to determine the feasibility of each sensor towards the design of the new rehabilitation monitoring device. The experiments demonstrate the capabilities of the sensors to produce extended information regarding arm movement activity which can be implemented in the design. A liquid crystal display (LCD) monitor will show to the user the achievement of their exercise activity on daily basis.